(untitled) (Journal of the College of Basic Education, 2020)
The current research aimed to measure the life skills of kindergarten children as a whole and to know the significance of gender differences. The research sample consisted of (100) children and girls from the preparatory grade aged (5-6) 50 children and 50 girls in the Directorate of Rusafa in Baghdad has been used to measure the life skills prepared by the researcher to measure the objectives set for research and verified the validity and stability and statistical analysis of the scale To analyze the results, a one-ti test was used and two independent samples were used to extract differences for the sample as a whole and for gender differences. Recommendations and proposals will be developed in light of the results